Formation of exocyclic olefinic groups via stereoselective nitrosations: a new route towards pendant arm macrocyclic ligands - Bernhardt, Paul V.; Comba, Peter (Journal of the Chemical Society. Chemical communications, 1993)
Nitrosation of the CuII and PdII complexes of trans-6,13-dimethyl-1,4,8,11-tetraazacyclotetradecane-6,13-diamine results in new macrocyclic complexes bearing exclusively exocyclic olefinic groups as shown by an X-ray crystal structure and NMR spectroscopy.
Gesehen am 02.09.2022